The promised neverland. Volume 17, The imperial capital battle - Shirai, Kaiu (Shonen Jump manga., 2020)
"The children of the Grace Field House orphanage must escape a macabre fate before it's too late. Life at Grace Field House is good for Emma and her fellow orphans. While the daily studying and exams they have to take are tough, their loving caretaker provides them with delicious food and plenty of playtime. But perhaps not everything is as it seems. In order to wipe out the demons, Norman sends his forces into the capital to take down the queen and the five aristocrat families. Emma also heads into the demon city with the intent of stopping Norman from doing something he'll regret. But can she get there in time?"--Provided by publisher.